Understanding the transition from career to fulltime motherhood: a qualitative study. - Vejar CM; Madison-Colmore OD; Ter Maat MB (American Journal of Family Therapy)
According to the literature, minimal research has been conducted on fulltime mothers (i.e., stay-at-home mothers [SAHM]); studies dealing with motherhood tend to emphasize the developmental needs of the child versus the mother. The current research seeks to tackle that issue by bringing fulltime motherhood to the forefront. In particular, phenomena related to women transitioning from work to fulltime motherhood are qualitatively examined. Four women participated in this study and shared their personal experiences surrounding this subject matter. A SAHM Model and two SAHM Portraits are created to comprehend and explain the complexities found within their roles.